O06.1 Evaluation of 5 Different Tests For Trichomonas Vaginalis (TV) Infection and Cost Effective Planning For Clinical Implementation. (13th July 2013) - Nathan, B; Appiah, J; Heron, D; Saunders, P; Brum, R; Alexander, S; Baraitser, P; Ison, C
Abstract : Background: TV is the most common non-viral STI in the world. Despite this, TV infection in UK Genitourinary clinics is mainly (and often exclusively) diagnosed by wet mount microscopy alone. Microscopy is known to have a low and variable sensitivity and therefore greatly underestimates the true prevalence of TV infection. Objectives: A clinical trial was conducted to evaluate the performance of five methods for detecting TV: an in-house PCR; the Aptima TV kit; the OSOM Trichomonas Rapid Test (POCT); culture and microscopy to diagnose infection in symptomatic women. The results of the study were used to power a financial model for clinical implementation of a molecular test. Methods: Symptomatic women were recruited for testing. Results and resource costs from the study were extrapolated to calculate the cost of implementing POCT and in house PCR compared to wet mount microscopy in the clinic. Results: A composite reference standard of 2 more or more positives was used. 246 women were recruited of which 24 had a positive test by 2 or more of the 5 methods. Aptima TV kit, POCT, Real-time PCR and culture (sensitivities 92, 92, 88 and 88%) all out performed wet-mount microscopy (sensitivity 38%). The prevalence based on two tests as reference standard was 9.75%. Conclusions: Cost modelling showed although initial outlay costs for PCR and POCT were high, savings were made in labour costs. PCR and POCT would improve the rate of TV diagnosis in this group and therefore reduce repeat visits due to false positive results. PCR requires additional clinical time for recalling the patient for a further visit to give a positive result, treatment and contact tracing. Implementation of newer tests could potentially reduce clinical cost and improve patient outcomes in the long term.